1983
DOI: 10.1016/s0022-5347(17)51695-x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Bladder Cancer: Progression and Recurrence

Abstract: The tumors in 249 patients presenting initially with stages Ta and T1 bladder cancer were analyzed for tumor progression and recurrence. Only transurethral resection and/or fulguration was used before the first recurrence. Patients who received intravesical chemotherapy after the first tumor recurrence were excluded from an analysis of progression. Progression according to stages Ta and T1, and grades I, II and III was 4, 30, 2, 11 and 45 per cent, respectively. All differences were statistically significant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
316
2
13

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 860 publications
(346 citation statements)
references
References 7 publications
15
316
2
13
Order By: Relevance
“…Although ted that cyclin Dl is metastasis is less common with superficial bladder cancers, such cell cycle (Xiong et al, tumours may progress and the majority will recur and require s involved in cell cycle additional treatment. It is generally accepted that patients with TI, ) and other cell cyclemultiple, large or high-grade tumours are at greater risk of recurfinds et al, 1992; Xiong rence (Heney et al, 1983;Wolf et al, 1985). In this study, we assessed the probability of disease-free survival in the 53 superostic significance of the ficial tumours according to the overexpression of cyclin Dl.…”
Section: Discussionmentioning
confidence: 99%
“…Although ted that cyclin Dl is metastasis is less common with superficial bladder cancers, such cell cycle (Xiong et al, tumours may progress and the majority will recur and require s involved in cell cycle additional treatment. It is generally accepted that patients with TI, ) and other cell cyclemultiple, large or high-grade tumours are at greater risk of recurfinds et al, 1992; Xiong rence (Heney et al, 1983;Wolf et al, 1985). In this study, we assessed the probability of disease-free survival in the 53 superostic significance of the ficial tumours according to the overexpression of cyclin Dl.…”
Section: Discussionmentioning
confidence: 99%
“…However, such tumors infiltrating the lamina propria underwent TUR or cystectomy. 19 In 1983, Heney et al 20 showed progression in 4% of Stage Ta and 30% of Stage T1 tumors, with the progression-free interval significantly shorter for those with Stage T1 than for those with Stage Ta tumors (P Ͻ .001). These investigators also analyzed progression by grade within stage and showed that progression occurred in 21% of T1G2 tumors.…”
Section: Commentmentioning
confidence: 99%
“…The investigators stated that, "our findings also underscore strongly the difference in prognosis between tumors that are confined to the mucosa and those that have already invaded the lamina propria" and observed that such invasion is associated with a decrease in 5-year survival. 20 Holmang et al 21 provided follow-up results obtained from 176 patients with primary Ta or T1 tumor. They were treated by TUR and followed up for 20 years or until death.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Approximately 80% of primary bladder cancers are papillary noninvasive or superficially invasive lesions (stage Ta and T1) and can be managed by local endoscopic resection. A special feature of these tumors is the high recurrence rate of about 50% after transurethral resection, 2,3 and patients with recurrent bladder cancer, especially those with high-grade or multifocal lesions, are at significant risk for stage progression and death from the disease. 3,4 On the other hand, papillary bladder cancer comprises different types of tumors with varying biologic potential and distinct pathways of development.…”
mentioning
confidence: 99%